2006
DOI: 10.1007/s10038-006-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Unique origin of Andaman Islanders: insight from autosomal loci

Abstract: Our mtDNA and Y chromosome studies lead to the conclusion that the Andamanese ''Negrito'' mtDNA lineages have survived in the Andaman Islands in complete genetic isolation from other South and Southeast Asian populations since the initial settlement of the region by the out-of-Africa migration. In order to obtain a robust reconstruction of the evolutionary history of the Andamanese, we carried out a study on the three aboriginal populations, namely, the Great Andamanese, Onge and Nicobarese, using autosomal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The M4 lineage shares some mutations with the M4 lineage from the Semende, but each have several unique mutations. Subgroups of M4 have been previously reported in tribal populations in India 18,19 , Nepal 20 and in the Philippines 21 . There is thus a striking dichotomy in the mtDNA lineages between the matrilocal Semende and the patrilocal Besemah.…”
Section: Discussionmentioning
confidence: 76%
“…The M4 lineage shares some mutations with the M4 lineage from the Semende, but each have several unique mutations. Subgroups of M4 have been previously reported in tribal populations in India 18,19 , Nepal 20 and in the Philippines 21 . There is thus a striking dichotomy in the mtDNA lineages between the matrilocal Semende and the patrilocal Besemah.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, we indicated that Deng might have developed from very few founders, and been isolated from the neighboring Adi and Tibetans for quite long time. However, compared with the results of the Andamanese 73 by the same analyses, the time isolated of Deng should be much shorter. Judging from the phylogenetic tree and the MDS plot, Deng is closer to the Adi populations than to the Tibetans.…”
Section: Genetic Structure Of Deng Populationmentioning
confidence: 80%
“…These results were similar to those of the other isolated populations previously reported. 13,[73][74][75] Lower gene diversity of Deng (0.7218) further accentuated the effect of the inbreeding among them. Therefore, we indicated that Deng might have developed from very few founders, and been isolated from the neighboring Adi and Tibetans for quite long time.…”
Section: Genetic Structure Of Deng Populationmentioning
confidence: 99%
“…There is some evidence that genetic variation among the Andaman Islanders may reflect considerable isolation following initial dispersal out of Africa (Kashyap et al 2003;Thangaraj et al 2003Thangaraj et al , 2006Thangaraj and Chaubey 2005). Although this plausibly fits an interpretive framework where the Andaman Islanders and other negrito populations represent relict populations of this early dispersal, recent evidence suggests that genetic variation among these populations is much more complex than previously thought (Reich et al 2009).…”
Section: Negrito Populations and Theirmentioning
confidence: 89%
“…Subsequent research using mitochondrial DNA (mtDNA) variation provided evidence for a link between negrito groups of the Andaman Islands and sub-Saharan African foragers (Mukerjee 1999). More recent research has enhanced our understanding of the genetics of this group, suggesting that genetic variation among the Andaman Islanders may reflect considerable isolation of this population following initial dispersal out of Africa (Thangaraj et al 2003(Thangaraj et al , 2006Thangaraj and Chaubey 2005). Although this plausibly fits an interpretive framework where the Andaman Islanders and other negrito populations represent relict populations of this early dispersal, recent evidence suggests that genetic variation among negritos is complex (Reich et al 2009).…”
mentioning
confidence: 99%